Is nasal packing necessary after septoplasty? A meta‐analysis. Issue 5 (7th November 2012) - Banglawala, Sarfaraz M.; Gill, Mandeep; Sommer, Doron D.; Psaltis, Alkis; Schlosser, Rodney; Gupta, Michael
<x xml:space="preserve">Abstract</x> Background Nasal packing is routinely used after septoplasty because it is believed to decrease risk of postoperative bleeding, hematomas, and adhesions. Multiple studies have shown, however, that there are numerous complications associated with nasal packing. The purpose of this work was to perform a meta‐analysis on the existing literature to evaluate the role of nasal packing after septoplasty. Methods Two independent reviewers conducted a literature search using EMBASE, OVID, Medline, PubMed, Google scholar, Cochrane Library, and reference list review from 1966 to August 2010 to identify studies assessing nasal packing after septoplasty. All papers were reviewed for study design, results, and were assigned an Oxford level of evidence grade, Detsky score, and Methodological Index for Nonrandomized Studies (MINORS) score. Results Sixteen papers were identified that met the inclusion criteria. Eleven papers were randomized control trials, 3 were prospective, and 2 were retrospective studies. Nasal packing did not show benefit in reducing postoperative bleeding, hematomas, septal perforations, adhesions, or residual deviated nasal septum. There was, however, an increase in postoperative infections. Two studies using fibrin products as nasal packing showed a decreased bleeding rate. Conclusion Nasal packing after septoplasty does not show any postoperative benefits. Fibrin products show a possibility of decreasing postoperative bleeding. Routine use of nasal packing after septoplasty is not warranted. This is the first meta‐analysis conducted on this topic.